Navigating Hybridity and Female Empowerment in Anca’s Journey: A Feminist and Cultural Analysis of Migration and Identity - Hutahayan, Regine Juliana Leonora; Derick, Kenzie Cornelius; Roling, Nixon Dyllen; Jeswin, Oliver Rafael; Supriadi, Ben Othniel; Ang, Michelle Whitney (Jurnal Pendidikan Makarios, 2024)
This research examines Ruth Siburt’s ‘Anca’s Journey’ through the lenses of Liberal Feminism and Cultural Hybridity, focusing on how the story addresses traditional gender roles and the complexities of migration. Using Betty Friedan’s Liberal Feminism (1963) to explore themes of female empowerment through education and Homi K. Bhabha’s Cultural Hybridity (1994) to analyze identity negotiation as a secondary theory, As the results: 1) Anca’s Journey subverts traditional gender roles by portraying Anca’s intellectual growth as a central form of empowerment. Her education allows her to transcend societal expectations typically placed on young girls, aligning with Friedan’s feminist ideals. 2) The story highlights the resilience and agency of its female characters, particularly Anca and her mother, as they navigate societal pressures in a patriarchal, migration-focused narrative. Anca’s refusal to accept labels like "lame" demonstrates her resistance to restrictive social judgments, while her mother’s protective role illustrates maternal agency. 3) Anca's intellectual growth is a key factor in her ability to navigate her cultural environment, as she balances the expectations of her Romanian heritage with her new life in America. This reflects both feminist and hybrid identity formation theories. These findings illustrate how Anca’s Journey not only challenges traditional gender expectations but also reflects the broader social realities of migration, using education as a means of empowerment and identity negotiation.